Pragmatism of Smart Contracts in Legal Perspective: A Comparative Analysis Between Indonesia and The United States - Warianto, Wahyudi; Amboro, Florianus Yudhi Priyo; Sudirman, Lu (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
Smart Contracts offer significant potential for contractual processes in Indonesia, much like their utilization in the United States under the prevailing regulations of both countries, including the Electronic Information and Transactions Law Number 11 of 2008, the Civil Code, the Uniform Electronic Transaction Act, the Electronic Signatures in Global and National Commerce Act, the Blockchain Technology Act, as well as Arizona House Bill 2417 and Nevada Senate Bill No. 398. This study aims to pragmatically analyze the legal perspective regarding the legal capacity to facilitate the use of Smart Contracts as a form of blockchain technology, using the legal framework of the United States as a comparative basis. The research employs a comparative legal research method with a legislative approach. The analysis reveals the inadequacy of the legal framework in Indonesia, despite recent revisions, which still exhibit numerous shortcomings in facilitating the utilization of Smart Contracts. Suggestions for regulatory aspects are proposed to support comprehensive legal development, as an effort to adapt to the evolving times. Smart Contract menawarkan potensi pemanfaatan yang baik dalam proses berkontrak di Indonesia, sebagaimana yang telah mulai dimanfaatkan di Amerika Serikat melalui peraturan perundag-undangan yang berlaku di kedua belah negara, yaitu Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik, Kitab Undang-Undang Hukum Perdata, Uniform Electronic Transaction Act, Electronic Signatures in Global and National Commerce Act, Blockchain Technology Act, dan Arizona House Bill 2417, Nevada Senate Bill No. 398. Penelitian ini bertujuan untuk menganalisis secara pragmatisme dalam perspektif hukum perihal kecakapan hukum untuk memfasilitasi pemanfaatan Smart Contract sebagai bentuk teknologi blockchain, dengan menggunakan kerangka hukum Amerika Serikat sebagai bahan komparasi. Penelitian ini menggunakan metode penelitian komparatif dengan pendekatan perundang-undangan. Analisis menemukan adanya ketidakcakapan kerangka hukum di Indonesia, meskipun telah didukung dengan revisi pengaturan terbaru, yang nyatanya masih memiliki banyak kekurangan dalam kecakapan untuk memfasilitasi pemanfaatan Smart Contract. Usulan aspek pengaturan diusulkan oleh pengaturan ini untuk mendukung perkembangan hukum yang komprehensif, sebagai upaya beradaptasi terhadap perkembangan zaman